Investigating pre-harvest and postharvest interventions to control foodborne pathogens and surrogates on lettuce - Jenott, Jacob Robert (Kansas State University, 2017)
Leafy greens have been recognized as vehicles for transmission of foodborne pathogens and an effective pre-harvest intervention to control them is currently lacking. After harvest, lettuce is often subjected to chlorinated water to reduce the microbial load in the water and on the lettuce tissue. While moderately effective, there is also a need for improved postharvest interventions. The purpose of Objective I was to 1) determine potassium bisulfate efficacy at reducing populations of Escherichia coli (E. coli) and Listeria innocua (L. innocua) when applied pre-harvest to lettuce, and 2) assess the impact on product quality at harvest. Potassium bisulfate reduced E. coli populations on inoculated lettuce by 1.32 log₁₀ CFU/g (P=0.0002) and L. innocua by 1.18 log₁₀ CFU/g (P=0.0017). No detectable differences were observed in color (P>0.05); however, brown spots were observed on various leaves sprayed with potassium bisulfate. The purpose of Objective II was to employ a blend of benzalkonium chloride, acetic acid, and methyl paraben (BAM) as a postharvest wash on romaine and iceberg lettuce and to 1) determine efficacy at reducing populations of Listeria monocytogenes (L. monocytogenes), E. coli O157:H7 and Salmonella, 2) measure changes in aerobic bacteria throughout the shelf life, and 3) quantify benzalkonium chloride and methyl paraben residues post-washing. To quantify efficacy of BAM reducing pathogenic bacterial populations, fresh-cut romaine and iceberg lettuce were inoculated with L. monocytogenes, E. coli O157:H7, or Salmonella and washed in BAM at concentrations of 0%, 1%, 2% or 3% for one or five minutes. When plated on recovery media, contact time and wash concentration was not significant (P>0.05) for Salmonella on either product. Concentration was significant (P=0.0189) for L. monocytogenes on romaine; however, the greatest reduction observed was <1.0 log₁₀ CFU/g. The 3% wash significantly reduced E. coli O157:H7 on romaine by 1.75 log₁₀ CFU/g, which is 0.66 log₁₀ CFU/g better than the 0% wash. Following washing, wash water was analyzed and data demonstrate that all wash concentrations significantly (P≤0.05) reduced each foodborne pathogen by >2.0 log₁₀ CFU/g in the wash water. To quantify benzalkonium chloride and methyl paraben residues, as well as changes in aerobic bacteria and product quality, fresh-cut romaine and iceberg lettuce were subjected to a 1 minute wash in BAM at concentrations of 0%, 1%, 2%, or 3% and immediately sampled to determine aerobic populations and product quality. Concentrations 0% and 2% were also packaged into retail storage bags and sampled on days 0, 3, 5, and 7. Residues were quantified on these days as well. On day 0, aerobic populations did not vary according to wash concentration (P>0.05). With regards to shelf-life data, the 2% wash significantly reduced (P=0.0203) aerobic bacteria on romaine lettuce; however, no significant difference was observed on iceberg lettuce (P=0.0819). With regards to overall visual appearance of romaine or iceberg lettuce, no significant difference was detected between 0% and 2% BAM washes for each day throughout the shelf-life study (P>0.05). Methyl paraben and benzalkonium chloride residues were <5.0 and <10.0 ppm, respectively, on both products on each sampling day.
Keywords: Pre-harvest; Postharvest; Lettuce; Potassium bisulfate; Benzalkonium chloride